Eletrodinâmica quântica de guias de onda com aplicações na termometria quântica - Dourado, Sinara Santos (2022)
Advances on quantum technologies, such as quantum computation and quantum sensing, and the miniaturization of electronic components make metrology protocols and fine control of temperature at the quantum scale a pressing problem. In this dissertation we propose a thermometry protocol using waveguide quantum electrodynamics. We start by revisiting the fundamentals. First, we study the classical model of interaction of light with matter, the Lorentz model, as well as the emission spectrum due to temperature and the thermal effect that an electromagnetic field from a thermal source has on an electric dipole according to the Lagevin model. In addition, we study the quantization of the energy levels of matter and the electromagnetic field, as well as the interaction between them. Our theory makes use of the Heisenberg picture and coherent states to calculate the evolution of a system composed of an atom coupled to a waveguide on which we focus a laser, obtaining the Bloch equations that describe this system. We also calculated the reflectance and transmittance of the electromagnetic field resulting from the interaction with the atom, which are the quantities that can be measured in a laboratory and that showed us the purely quantum effects of the atom-field interaction. Finally, we assume that the atom coupled to the waveguide had been in contact with a thermal bath, being therefore in a thermal initial state, and again we propose the interaction with the laser. We analytically calculate the reflected and transmitted powers to determine the temperature of the atom. In fact, this protocol proved to be effective in determining the initial temperature of the atom and surprised us by showing that an atom at a high initial temperature has all its dynamics affected, undergoing decoherence of characteristic quantum phenomena such as stimulated emission.